The Protective Effects of Origanum vulgare L. Extract on Genetic Damage of Cyclophosphamide in Mice Blood Lymphocytes Using Micronucleus Test - Mohammad Shokrzadeh; Emran Habibi; Amir Shadboorestan; Aroona Chabra; Amirhossein Ahmadi (Pharmaceutical and Biomedical Research, 2020)
Background: Despite its various clinical applications, cyclophosphamide (CP), an alkylating chemotherapeutic agent, has demonstrated numerous side effects, including genetic toxicity. Objectives: This study investigated the protective action of Origanum vulgare L., a powerful antioxidant plant, on the genotoxicity of CP in the mice blood lymphocytes. Methods: The mice were pre-treated orally with different doses of 50, 100, 200, or 400 mg/kg O. vulgare ethanolic extract once a day for 7 consecutive days. One hour after the final dose of O. vulgare, each animal received a single intraperitoneal administration of 200 mg/kg CP. After 24 hours, the preventive effect of O. vulgare was evaluated using an in vitro micronucleus (Mn) test in cytokinesis-blocked lymphocytes, which is a reliable genotoxicity test. All doses of O. vulgare caused significant reductions in the CP-induced Mn formation, which served as an indicator of DNA damage in the peripheral blood lymphocytes. Results: The total reduction of the Mn in binucleated lymphocytes were 67% and 75% for doses of 200 and 400 mg/kg of O. vulgare, respectively (P<0.001). The antioxidant plant demonstrated dose-dependent protective effects against CP-induced Mn formation and genotoxicity in the blood lymphocytes of the mice. O. vulgare can reduce the damage to DNA through its potent antioxidation activity and free radical scavenging properties. Conclusion: Since it is widely used as a safe herbal medicine for many diseases, O. vulgare could be used to relieve the adverse effects of cyclophosphamide, especially against the genetic damages of normal cells in patients undergoing chemotherapy.